Impact of child and family characteristics on cerebral palsy treatment. (8th May 2015) - Rackauskaite, Gija; Uldall, Peter W; Bech, Bodil H; Østergaard, John R
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to describe the relationship between the child's and family's characteristics and the most common treatment modalities in a national population‐based sample of 8‐ to 15‐year‐old children with cerebral palsy. Method A cross‐sectional study, based on the Danish Cerebral Palsy Registry. The parents of 462 children answered a questionnaire about their child's treatment and the family's characteristics (living with a single parent, having siblings, living in a city, parental education level). Descriptive and logistic regression analyses were performed for every treatment modality, stratified by Gross Motor Function Classification System (GMFCS) level. Results An IQ below 85 was associated with weekly therapy in GMFCS level I (adjusted odds ratio [ORadj] 2.5 [CI 1.1–5.7]) and the use of oral spasmolytics in GMFCS levels III to V (ORadj 3.1 [CI 1.3–7.4]). Older children in GMFCS levels III to V used daily orthoses less frequently (ORadj 0.7 [CI 0.6–0.9] per year). Of all of the family characteristics studied, only the parents' education level had significant associations with more than one treatment modality. Interpretation A child's cognitive function showed an impact on treatment of the motor impairment in children 8 to 15 years of age with cerebral palsy. Parental education level may influence the choice of treatment.